THE INFLUENCE OF EXTREMELY LOW FREQUENCY (ELF) MAGNETIC FIELD EXPOSURE ON THE PROCESS OF MAKING CREAM CHEESE - Andika Kristinawati; Sudarti Sudarti (UPT Penerbitan Universitas Jember, 2016)
Extremely Low Frequency (ELF) Magnetic field exposure in bacteria can impact the proliferation process. Cheese is one of the milk products produced by the process of fermentation using mesophilic and thermophilic bacteria. However, the taste of the cheese is commonly not good, bitter or too salty. It happens because the growth of mesophilic and thermophilic bacteria often fail. Thus, it needs an effective method to optimilize the growth of mesophilic and thermophilic bacteria. As the alternative solution, this research applies ELF magnetic field to activate the mesophilic and thermophilic bacteria. The intencity of the ELF magnetic field used 100 μT by the exposure of about 5 minutes, 20 minutes, 35 minutes, 50 minutes, and 65 minutes. The indicators used in this research are pH and moisture. The process of exposing ELF magnetic field was conducted in physics laboratory of Faculty of Teaching and Education University of Jember, while measuring pH was conducted in microbiology laboratory of Faculty of Teaching and Education University of Jember and measuring moisture was conducted in microbiology laboratory of Faculty of Mathematics and Sciences University of Jember. The result of this research confirmed that the pH and moisture at the controlled group are 5,50 and 85,6%. The pH and moisture at the exposed ELF magnetic field group 100 μT for 5 minutes and 20 minutes were lower than the controlled group. Based on the descriptive analysis, it can be seen that the decreasing happened at the 5 minutes exposed group at the time of 25 and 30 after the exposed ELF magnetic field. Therefore, it can be concluded that the effective dose to reduce the pH and moisture is the exposure to the ELF magnetic fields of 100 μT for 5 minutes.